2020
DOI: 10.1002/essoar.10501617.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the 2018 Ambae eruption on the global stratospheric aerosol layer and climate

Abstract: Various satellite data reveal a significant impact on the global stratosphere.• Radiative forcing values similar to that of recent moderate volcanic eruptions was found.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 10 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…How well do your results agree with e.g. Kloss et al, 2020; other estimates of Ambae/Aoba SO 2 mass injections (https://so2.gsfc.nasa.gov/omi_2004_now.html)? Did you expect that the ECHAM simulation reproduces the plume correctly?…”
Section: Interactive Commentsupporting
confidence: 60%
“…How well do your results agree with e.g. Kloss et al, 2020; other estimates of Ambae/Aoba SO 2 mass injections (https://so2.gsfc.nasa.gov/omi_2004_now.html)? Did you expect that the ECHAM simulation reproduces the plume correctly?…”
Section: Interactive Commentsupporting
confidence: 60%
“…Over the longer term, three to four weeks after the climactic eruption, Sellitto 46 showed that the water vapor's TOA radiative forcing switched sign (due to decreased altitude) and was +0.8 Wm −2 , thus canceling out the cooling impact of aerosols 46 ). For comparison, the aged plume TOA for large recent volcanic eruptions (e.g., Raikoke 2019, Ambae 2018) and wildfires (e.g., Australian bushfires 2019-2020), as well as the Pinatubo 1991 eruption 47,48 , are typically negative with values ranging from −3.5 (Pinatubo) to −0.3 Wm −2 .…”
Section: Discussionmentioning
confidence: 99%
“…This paper focuses on observations by NASA's OMPS LP instrument, which has previously made observations of smaller eruptions including Kelut (2014), Calbuco (2015), Ambae (2018), Ulawun (2019) and Raikoke (2019) (Gorkavyi et al., 2021; Kloss et al., 2020, 2021; Tadiga et al., 2022). Due to the unusual strength of the eruption, aerosol is observed at altitudes that far exceed the normalization altitude for the standard OMPS LP aerosol retrieval algorithm (above which aerosol scattering is assumed to be negligible).…”
Section: Introductionmentioning
confidence: 99%